2017
DOI: 10.3390/nu9030204
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low Carbohydrate Diets on Fertility Hormones and Outcomes in Overweight and Obese Women: A Systematic Review

Abstract: (1) Background: Medical interventions including assisted reproductive technologies have improved fertility outcomes for many sub-fertile couples. Increasing research interest has investigated the effect of low carbohydrate diets, with or without energy restriction. We aimed to systematically review the published literature to determine the extent to which low carbohydrate diets can affect fertility outcomes; (2) Methods: The review protocol was registered prospectively with Prospective Register for Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
0
38
0
2
Order By: Relevance
“…In this context KDs could be considered, as a nutraceutical therapy aimed to increase insulin sensitivity. The data available in the literature [26,[30][31][32], although few, confirm the assumption that a KD, correcting hyperinsulinemia and improving body composition, can contribute to the normalization of the clinical picture in PCOS. During fasting or a carbohydrate restriction such as a KD, blood insulin concentration decreases, while glucagon increases to maintain the normal blood glucose level, first through glycogen stores, then through the β-oxidation of fatty acids stored in fat depots.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this context KDs could be considered, as a nutraceutical therapy aimed to increase insulin sensitivity. The data available in the literature [26,[30][31][32], although few, confirm the assumption that a KD, correcting hyperinsulinemia and improving body composition, can contribute to the normalization of the clinical picture in PCOS. During fasting or a carbohydrate restriction such as a KD, blood insulin concentration decreases, while glucagon increases to maintain the normal blood glucose level, first through glycogen stores, then through the β-oxidation of fatty acids stored in fat depots.…”
Section: Discussionmentioning
confidence: 96%
“…In PCOS, evidence for the effects of KD are scarce: only a small uncontrolled pilot study [29] showed a significant reduction in body weight, free testosterone, LH to FSH ratio, and fasting insulin after a KD regimen, suggesting favourable effects in affected patients. Other data describe several mechanisms consistent with the favourable effects of such diet therapy [30][31][32]. A recent position statement of the Italian Society of Endocrinology suggested a weight-loss program with a very low calorie ketogenic diet for overweight/obese patients with PCOS) not responsive to multicomponent standardized diet to improve insulin resistance, ovulatory dysfunctions and hyperandrogenemia, even if further controlled studies are deemed necessary to confirm the beneficial effects of KD in this clinical context [28].…”
mentioning
confidence: 91%
“…Preliminary evidence of positive metabolic and endocrinological outcomes, in terms of reduced body weight, free testosterone, LH and fasting insulin levels, has been also reported on a calorie-restricted, very-low carbohydrate, ketogenic diet (VLKD) [133]. On the other hand, it is still uncertain for how long a very-low carbohydrate dietary pattern can be followed to achieve the best outcome without resulting in potential safety concerns [133,134]. In contrast, the effects of the MedDiet on PCOS outcomes have attracted intense interest in the last few years [135,136].…”
Section: Meddiet and Resveratrol In Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%
“…Similarly, a retrospective cohort study including 120 patients showed that a diet composed of a protein intake greater than 25% combined with a carbohydrate intake lower than 40% is related to better blastocyst development and pregnancy rates (Russell et al, 2012). However, a recent systematic review concluded that there is not enough evidence to support low-carbohydrate diets for infertile women without PCOS (McGrice and Porter, 2017).…”
Section: Bioactive Molecules Antioxidants and Calorie Restrictionmentioning
confidence: 99%